IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KABUPATEN KONAWE - Sukarmin, Sukarmin (EDUTECH CONSULTANT, 2019)
This study aims to identify and analyze: (1) Determine and analyze the implementation of waste management policy in Konawe and (2) the factors that affect the implementation of waste management policy in Konawe. This research use desciptive qualitative approach. Gathering data using a technique, observation, interviews and document research. Research data analysis using qualitative analysis techniques interactive model. The results of this study indicate that (1) Implementation of waste management policy in Konawe regency implemented because: (a) the objectives of improving the hygiene, health and quality of a healthy environment, conducive, comfortable and orderly. (b) the activities for achieving the goals, which is doing the planning and implementation of waste management activities such as waste separation, waste collection, waste transport, waste treatment and final processing of garbage, and (c) the results of the activities that waste management can improve the hygiene, public health and environmental quality in Konawe regency. (2) the factors that determine the implementation of waste management policy in Konawe, namely (a) the communication, the interaction between leaders and subordinates, between work units with other work units, and between fellow employees to submit ideas for waste management in Konawe regency, (b) resources, such as information, authority, employees or staff, supervisors, drivers junk cars, mobile workers and the availability of junk cars, motorbikes garbage, landfills and landfills can determine the effectiveness of waste management in Konawe regency, ( 3) the disposition of the attitude of the employees, managers and employees on duty in the field because it is supported by incentives and (4) the structure of the bureaucracy, the waste management division of duties so that there is implementation of waste management policy can be implemented effectively to achieve the objectives as planned.